Identifikasi Gaya Pengasuhan Ibu Bekerja dan Ibu Tidak Bekerja Terhadap Perilaku Sosial Anak Usia Dini - Maarang, Martheda; Netry Maria Lily; Norlianti Lusia Tabun; Petrus Mau Tellu Dony (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2025)
Parenting style is a form of behavior given by adults to children by providing quality time with family and paying attention to children as a form of affection, Many activities for working mothers reduce quality time with children, but mothers who do not work spend more time with children. This study aims to determine the parenting styles of working and non-working mothers in the Welai Timur-NTT Village—research using descriptive quantitative methods. The data collection method uses a Google form questionnaire. Data analysis using the descriptive statistical analysis method was analyzed with the help of the average formula. The results of the research from 36 respondents that the parenting style that is often applied is democratic parenting with the percentage of working mothers at 46%, permissive at 28%, and authoritarian at 26%, and mothers who do not work with a percentage of democratic parenting style 42%, permissive 30%, and authoritarian 28%. Children who grow up in democratic parenting bring up positive energy, increase creativity, and have high self-confidence. It is recommended to apply a democratic parenting style to children